What if all countries were actually in the same boat? A comparison of countries' vulnerability based on Markov Switching Models - Brendan Vannier (FIW - Research Centre International Economics, 2016)
This article aims at assessing the main characteristics of the business cycle of 80 developed and developing countries. By comparing the possibility for these economies to enter or to exit a recession and the associated consequences, it aims at complementing existing literature with regard to scale and/or frequency of the study. Following the usual definition of a recession, an algorithmic classification tends to show that, surprisingly, developed and developing countries face similar probabilities to enter or to exit a recession, respectively around 5% and 18%. This aspect contradicts existing literature, which often advocates a greater volatility of developing countries' business cycle with more frequent recessions. However emerging markets and economies face output per capita losses around twice as important as advanced ones when they undergo a recession. These observations are then tested using a non-linear parametric Markov-Switching Model. If the statistical validity of this method is bound by data availability, it echoes in a really good manner the pattern derived using a non-parametric approach. Estimating the model on the cyclical component of the series, derived using an HP filter, fits the best previous remarks. It also replicates other major characteristics. Indeed while developed countries form a rather homogeneous group, developing countries demonstrate greater heterogeneity. Latin American countries appear as the most vulnerable ones whereas Asian countries perform better than all other groups.
Keywords: F43; C32; O57; 330; business cycles; economic growth; vulnerability; Markov Switching Models